1987
DOI: 10.1128/aem.53.10.2511-2519.1987
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of chloroguaiacols, chloroveratroles, and chlorocatechols by stable consortia of anaerobic bacteria

Abstract: Metabolically stable consortia of anaerobic bacteria obtained by enrichment of sediment samples with 3,4,5-trimethoxybenzoate (TMBA), 3,4,5-trihydroxybenzoate (gallate [GA]), or 5-chlorovanillin (CV) were used to study the anaerobic transformation of a series of chloroveratroles, chloroguaiacols, and chlorocatechols used as cosubstrates. Experiments were carried out with growing cultures, and the following pathways were demonstrated for metabolism of the growth substrates: (i) TMBA produced GA, which was furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 53 publications
2
39
2
Order By: Relevance
“…(b) The more highly chlorinated congeners appear generally to be more readily dechlorinatcd which is consistent with the hypothesis that dechlorination is an energy-producing reaction coupled to metabolism of the substrate (Dolfing 1990;Mohn & Tiedje 1990). The corresponding reactions with the bromo analogues have not been systematically investigated, although debromination was one of a series of reactions observed during the metabolism of Sbromovanillin-but not 5-chlorovanillin-by stable anaerobic consortia (Neilson et a/.…”
Section: Deblogenation Of Aromatic Compounds Under Anaerobic Conditionssupporting
confidence: 73%
“…(b) The more highly chlorinated congeners appear generally to be more readily dechlorinatcd which is consistent with the hypothesis that dechlorination is an energy-producing reaction coupled to metabolism of the substrate (Dolfing 1990;Mohn & Tiedje 1990). The corresponding reactions with the bromo analogues have not been systematically investigated, although debromination was one of a series of reactions observed during the metabolism of Sbromovanillin-but not 5-chlorovanillin-by stable anaerobic consortia (Neilson et a/.…”
Section: Deblogenation Of Aromatic Compounds Under Anaerobic Conditionssupporting
confidence: 73%
“…The significant difference between estimates of recoverability based on short-term laboratory spike experiments and those based on work with naturally aged contaminated samples is readily illustrated by data from our own experiments. Previous studies using spiked sediment samples incubated in the laboratory under anaerobic conditions [21] and experiments using stable consortia have shown that, under anaerobic conditions, chloroguaiacols are rapidly de-0-methylated to chlorocatechols before dechlorination [29]. These results are in apparent conflict with the data presented here, which unequivocally show that substantial amounts of chloroguaiacols can, in fact, be recovered from natural samples of contaminated sediments.…”
contrasting
confidence: 99%
“…Reference samples of the chloroguaiacols, chlorocatechols and chlorovanillins were synthesized in this laboratory [28,29]. Quantitative analysis of all of the chloro compounds was carried out using GC analysis of the 0-acetates, as described previously [30].…”
Section: Procedures For Analysis a N D Identificationmentioning
confidence: 99%
“…In the absence of molecular oxygen, the aryl halogens of homocyclic *To whom correspondence may be addressed. aromatic compounds are biologically removed by reduction [12,18].…”
Section: Introductionmentioning
confidence: 96%